Move and countermove: the integrated stress response in picorna- and coronavirus-infected cells - Aloise, Chiara; Schipper, Jelle G; de Groot, Raoul J; van Kuppeveld, Frank Jm (Elsevier Ltd, 2022)
Viruses, when entering their host cells, are met by a fierce intracellular immune defense. One prominent antiviral pathway is the integrated stress response (ISR). Upon activation of the ISR - typically though not exclusively upon detection of dsRNA - translation-initiation factor eukaryotic initiation factor 2 (eIF2) becomes phosphorylated to act as an inhibitor of guanine nucleotide-exchange factor eIF2B. Thus, with the production of ternary complex blocked, a global translational arrest ensues. Successful virus replication hinges on effective countermeasures. Here, we review ISR antagonists and antagonistic mechanisms employed by picorna- and coronaviruses. Special attention will be given to a recently discovered class of viral antagonists that inhibit the ISR by targeting eIF2B, thereby allowing unabated translation initiation even at exceedingly high levels of phosphorylated eIF2.
Keywords: Apoptosis; Degradation; Inhibition; Leader protein; Messenger-rna; Mouth-disease virus; Nucleotide exchange; Phosphorylation; Protein-kinase; Translation; Immunology and Allergy; Immunology